Comprehensive Islamic Studies (Political Existence in Islam) - Muhammad Komarudin; Aflatun Muchtar; Rosidin Hasan (PT FORMOSA CENDEKIA GLOBAL, 2022)
In principle, society cannot be separated from politics, because society is a zoon politico that always wants to live together. Reflection of politically realized desires. In politics, people can master the potential that is spread among themselves, channel synergy in the same direction, and understand differences. The presence of the Islamic religion brought by the Prophet Muhammad SAW guarantees the fulfillment of a human life that is physically and mentally prosperous. Islamic teachings present an ideal picture of how human endeavors respond to life and life in a meaningful way, including human relations that cannot be separated from politics.